Eight new species and two new records of Batriscenellus Jeannel (Coleoptera: Staphylinidae: Pselaphinae) from China and India - Jiang, Ri-Xing; Yin, Zi-Wei (Zootaxa, 2017)
Eight new species of the pselaphine genus Batriscenellus Jeannel (Batrisitae: Batrisini) are described from China and India: B. besucheti, new species (India: Meghalaya), B. carltoni, new species (India: Meghalaya and Assam), B. cuccodoroi, new species (India: Meghalaya), B. fanxingqiui, new species (China: Fujian), B. loebli, new species (India: Meghalaya), B. pengzhongi, new species (China: Guizhou), B. simplex, new species (China: Guangxi), and B. strictus, new species (China: Zhejiang). Habitus and major diagnostic features of the new species are illustrated. New distributional records for B. femoralis Yin & Li (China: Fujian, Hunan) and B. xijiaogongyuan Yin, Jiang & Chen (China: Jiangxi) are provided.